1997
DOI: 10.1037/0021-843x.106.2.298
|View full text |Cite
|
Sign up to set email alerts
|

Expressed emotion and causal attributions in the spouses of depressed patients.

Abstract: High levels of expressed emotion are thought to be related to the attributions relatives make about the causes of a patient's illness and problem behaviors. Causal attributions occurring during spontaneous speech in 43 spouses of depressed patients were examined. Consistent with theoretical prediction and with previous research in schizophrenia, high critical spouses were more likely than low critical spouses to attribute patients' symptoms and negative behaviors to factors that were controllable by and person… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
68
1
8

Year Published

2000
2000
2011
2011

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 104 publications
(88 citation statements)
references
References 24 publications
11
68
1
8
Order By: Relevance
“…Indeed, a number of authors have noted that the correlates of these variables are different (e.g. Miklowitz et al, 1984;Harrison and Dadds, 1992;Hooley and Licht, 1997), and our analysis of posttest data indicated they have differing predictive relationships with immediate outcome. These findings suggest that EE variables should be treated as separate constructs until combining them has been empirically justified.…”
Section: G Steketee and D L Chamblessmentioning
confidence: 69%
“…Indeed, a number of authors have noted that the correlates of these variables are different (e.g. Miklowitz et al, 1984;Harrison and Dadds, 1992;Hooley and Licht, 1997), and our analysis of posttest data indicated they have differing predictive relationships with immediate outcome. These findings suggest that EE variables should be treated as separate constructs until combining them has been empirically justified.…”
Section: G Steketee and D L Chamblessmentioning
confidence: 69%
“…Several studies of schizophrenia and depression have shown that high EE is related to personal, internal, and controllable attributions (Barrowclough et al, 1994;Brewin, MacCarthy, Duda, & Vaughn, 1991;Hooley & Licht, 1997;Wendel, Miklowitz, Richards, & George, 2000). Wendel et al (2000) found that high EE relatives made more personal and controllable attributions than low EE relatives, whereas stability and internality of attributions were not related to EE.…”
mentioning
confidence: 98%
“…Because high EE relatives believe the patient is in control of his or her behavior, they believe the patient must also be capable of modifying this behavior. Thus, relatives struggle to normalize the patient's behavior through negative feedback and controlling behavior of their own (Hooley & Campbell, 2002 Several studies of schizophrenia and depression have shown that high EE is related to personal, internal, and controllable attributions (Barrowclough et al, 1994;Brewin, MacCarthy, Duda, & Vaughn, 1991;Hooley & Licht, 1997;Wendel, Miklowitz, Richards, & George, 2000). Wendel et al (2000) found that high EE relatives made more personal and controllable attributions than low EE relatives, whereas stability and internality of attributions were not related to EE.…”
mentioning
confidence: 99%
“…It provides information about the patient's symptomatology. It also provides a spontaneous sample of the relative's speech that can be used for other research purposes, such as coding attributions (see Barrowclough, Johnston, & Tarrier, 1994;Hooley & Licht, 1997) or controlling behaviors (Hooley & Campbell, 2002). The CFI may also be flexible enough in its probes to allow it to be successfully modified for use in crosscultural research.…”
Section: Summary and Recommendationsmentioning
confidence: 99%